2013
DOI: 10.1167/iovs.13-11697
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Dependence of the Ocular Straylight

Abstract: Small-angle straylight in the eye is affected by the wavelength-dependent properties of the fundus. At those small angles, measurements using wavelengths near the peak of the spectral sensitivity of the eye might be better correlated with the visual aspects of straylight. However, the impact of fundus reflectance on the values of the straylight parameter at larger angles did not depend on the measuring wavelength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 25 publications
5
32
0
Order By: Relevance
“…The latter means that the effect of scattering will be greater, or better more noticeable, when the image has both high reflective and high absorbing areas, in the same way that visually, scattering is much more noticeable when driving at night, where the dynamic range is large due to the headlights, than when at day. A first result, is the consistently lower amount of scattering at green, compared to blue and red, which is in line with a previous study [18]. For the longer wavelengths, however, there is an additional parameter that needs to be taken into account: melanin pigmentation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The latter means that the effect of scattering will be greater, or better more noticeable, when the image has both high reflective and high absorbing areas, in the same way that visually, scattering is much more noticeable when driving at night, where the dynamic range is large due to the headlights, than when at day. A first result, is the consistently lower amount of scattering at green, compared to blue and red, which is in line with a previous study [18]. For the longer wavelengths, however, there is an additional parameter that needs to be taken into account: melanin pigmentation.…”
Section: Discussionsupporting
confidence: 90%
“…Using the method of optical integration [16,18] the wide angle PSF was reconstructed for various wavelengths and it was then used to compensate its effect in fundus imaging. This compensation had an effect on the contrast of the image with an increase of 8.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that light emitted towards the pupil from this layer is the result of forward scattering and reflections at interfaces such as vessels and sclera. This situation is more evident at certain wavelengths [8,9] in function of the absorption properties of the pigment epithelium [6].…”
Section: Introductionmentioning
confidence: 98%
“…A group of subjects was tested with photographic diffusers, introducing in this way specific amounts of straylight. The results were compared with those provided by two independent devices, a device providing psychophysically subjective measurements of the intraocular straylight [16] and an objective instrument [17] based on the optical integration principle [14,18] to optically quantify the amount of intraocular straylight.…”
Section: Introductionmentioning
confidence: 99%